2023
DOI: 10.3390/cells12162098
|View full text |Cite
|
Sign up to set email alerts
|

Lacking Immunotherapy Biomarkers for Biliary Tract Cancer: A Comprehensive Systematic Literature Review and Meta-Analysis

Giorgio Frega,
Fernando P. Cossio,
Jesus M. Banales
et al.

Abstract: Background: Immunotherapy has recently been incorporated into the spectrum of biliary tract cancer (BTC) treatment. The identification of predictive response biomarkers is essential in order to identify those patients who may benefit most from this novel treatment option. Here, we propose a systematic literature review and a meta-analysis of PD-1, PD-L1, and other immune-related biomarker expression levels in patients with BTC. Methods: Prisma guidelines were followed for this systematic review and meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…Xiaoli et al found that the serum L-phenylalanine level in patients with esophageal cancer was signi cantly higher than that in healthy controls, whereas tyrosine levels were signi cantly lower than those in healthy controls (13). Cheng et al found that serum L-phenylalanine concentration in patients with NSCLC was signi cantly elevated (7). Gabriella Cadoni et al found that high serum L-phenylalanine levels in head and neck cancer patients were associated with increased risk of advanced disease and reduced overall survival (OS)(46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiaoli et al found that the serum L-phenylalanine level in patients with esophageal cancer was signi cantly higher than that in healthy controls, whereas tyrosine levels were signi cantly lower than those in healthy controls (13). Cheng et al found that serum L-phenylalanine concentration in patients with NSCLC was signi cantly elevated (7). Gabriella Cadoni et al found that high serum L-phenylalanine levels in head and neck cancer patients were associated with increased risk of advanced disease and reduced overall survival (OS)(46).…”
Section: Discussionmentioning
confidence: 99%
“…However, if the patient's PD-L1 expression was negative, it is di cult to predict the e cacy of PD-1/PD-L1 inhibitors in patients(6). Based on our clinical ndings, even patients who do not express PD-1/PD-L1 can bene t from immunotherapy (7), whereas some patients with > 50% PD-1/PD-L1 expression still develop early treatment resistance. Therefore, the use of PD-1/PD-L1 expression alone to predict or evaluate treatment response is inaccurate.…”
Section: Introductionmentioning
confidence: 86%
“…10,38 Evidence at this point would suggest that those with MSI-H tumors or tumors with high tumor mutation burden (TMB-H) may have better response to immunotherapy, however, these markers may be seen in a minority of patients. [39][40][41][42][43] In fact, MSI-H and/or deficient mismatch repair (dMMR) may be seen in 2-2.5% of BTCs and TMB-H may be seen in <5% of BTCs. 43,44 Expression of PD-L1 may be most common, seen in approximately 25% of tumors.…”
Section: Limitations Of Immune Checkpoint Inhibition In Biliary Tract...mentioning
confidence: 99%
“…[39][40][41][42][43] In fact, MSI-H and/or deficient mismatch repair (dMMR) may be seen in 2-2.5% of BTCs and TMB-H may be seen in <5% of BTCs. 43,44 Expression of PD-L1 may be most common, seen in approximately 25% of tumors. 43 In TOPAZ-1, in patients with PD-L1 tumor area positivity ≥1%, those who received durvalumab had numerically longer survival compared to those who received placebo with chemotherapy, although did not achieve statistical significance (HR = 0.79, 95% CI = 0.61-1.00).…”
Section: Limitations Of Immune Checkpoint Inhibition In Biliary Tract...mentioning
confidence: 99%
See 1 more Smart Citation